Anteseden Job Satisfaction Pada Karyawan Bank BCA Kelapa Gading - Adam Tri Purdini Harahap, Resky; Robiatul Adwaiyah, Wiwik; Oki Berliyanti, Dita (GEMA EKONOMI, 2023)
This study aims to analyze the effect of internal marketing, emotional intelligence, servant leadership on job satisfaction at Bank BCA Kelapa Gading. This study used respondents obtained according to the criteria with the census sampling method (saturation sampling) of 124 respondents. This study used cross-sectional and data processing using multiple regression analysis with SPSS software version 25.0. The results of this study indicate that internal marketing has a positive effect on Job satisfaction, emotional intelligence has a positive effect on job satisfaction, servant leadership has a positive effect on Job satisfaction. From the results of this study it is hoped that it can provide input for company management to pay attention to emotional intelligence which has the smallest influence in this study, to improve emotional intelligence, management can provide skills and knowledge training, provide additional bonuses and appreciation so that employees feel satisfied in their work so that they can have a positive impact on the progress of the company